Effect of road surface deformations on lateral lane utilization and longitudinal driving behaviours - Aydin, Metin M.; Topal, Ali (Transport, 2016)
Various road surface deformations generally occur on urban and rural roads due to infrastructure, superstructure deficiencies and excessive heavy vehicle loads. In addition to driver-based errors, many accidents happen due to these mentioned surface deformations. This study aims to present lateral lane utilization and longitudinal driving behaviours on a two-lane deformed road. The effect of deformation on the tendency of drivers’ lane selection, lane utilization, and the movement in traffic flow will also be determined. For this purpose, parameters such as lateral position, speed, acceleration/deceleration and location data of vehicles travelling through four different deformation zones on a two-lane road in Izmir (Turkey), were collected. Based on the fact that in ideal conditions, distribution of lateral positions of vehicles in a lane is similar to normal distribution. The collected data was evaluated with chi-square (χ2) goodness of fit test to see if they are fit to normal distribution or not. This study concluded that if a deformation zone has wider area and less depth, it will be less effective on lateral lane utilization of vehicles. It was also obtained from the results that variation in other parameters such as deformation type, depth and height are associated with the lateral lane utilization of drivers. Additionally, the drivers’ characteristics such as perception and aggressiveness are seen as the most important factors influencing the longitudinal vehicle behaviours while passing through the deformation zones.